Analysis and recommendations for improving financial reporting – a case study of the Serbian company “Nectar” - Vesic, Tamara; Cogoljevic, Maja; Petronijevic, Jovan (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
This paper presents, in the form of a case study, the process of analysis of financial statements of the business entity "Nectar", which engaged in the processing of fruits and vegetables in the Republic of Serbiais (a country with a very large agricultural potential). The time aspect of the research covered the period 2015-2018. The aim of this paper is to evaluate the past achievements of the company and predict future achievements in the function of supporting the decision-making process. Furthermore, the aim of the research is to assess the financial result and financial position of a given company through the analysis of the structure and dynamics of total income and the distribution of total income, profitability and opportunities to improve the financial position. Quantifying the functional relationships that exist between balance sheet items is the goal of enabling a credible assessment of the financial position. The results indicate that “Nectar” operates stably in the observed period; furthermore, there was an increase in short-term placements, as well as capital items. The trend of business revenues shows moderate stagnation, with the largest gain in 2017. Finally, it was concluded that there is room for export activities, since revenues in the country are about 30% higher than revenues abroad, so one of the resulting recommendations is to turn to export activities.